The clarifying lawful overseas use of data (CLOUD Act): Counter-terrorism effort or reproduction of United States’ hegemony in cyberspace? - Gustian, Rizki Puji (Universitas Islam Malang, 2024)
Besides the emergence of new technology since the inception of technology industry 4.0, cyberspace has also emerged as a new spatial dimension apart from land, sea and air. Cyber security is not only tied to one region or country but has become a global issue. As a non-traditional security concern, cyberspace threats vary from state and non-state actors. The United States (US) responded to this threat by issuing the Clarifying Lawful Overseas Use of Data (CLOUD Act) policy. The CLOUD Act aims to give the US the legitimacy to gain access to data related to terrorism, violent crime, child exploitation, and cybercrime abroad that is stored with digital service providers from the US. This research tries to question why the United States uses the issue of terrorism in CLOUD Act. This research uses a non-traditional security perspective, namely, cyber security and human security in cyber space. Using qualitative methods with deductive approach utilizing the perspectives of Non-Traditional Security (NTS), this research sees the formation of the CLOUD Act as an exceptional US step involving the issue of terrorism, like other steps after the 9/11 tragedy. This article argues that the U.S. CLOUD Act strategically uses concerns about terrorism and cybercrime to legitimize exceptional measures for accessing data from U.S.-based digital platforms, reinforcing US hegemony in cyberspace. It highlights how this policy enables the US to exert global influence over digital infrastructures, often at the expense of privacy and multilateralism.